Endocrinologic Outcome Following Endonasal Transphenoidal Excision of Growth Hormone Secreting Pituitary Adenomas - Aafee, Ali; Khambu, Bikesh; Jha, Rajiv; Bista, Prakash (Journal of Karnali Academy of Health Sciences, 2023)
Background: Endonasal Transphenoidal Approach for excision of pituitary adenomas has been gaining popularity over the traditional microsurgical approach. The objective of this study is to assess the rate of hormonal recovery following endonasal transphenoidal excision of growth hormone secreting pituitary macroadenoma in out center.Methods: In this prospective observational study all cases subjected to endonasal transphenoidal excision of growth hormone secreting pituitary adenoma, during the study period from January 2019 to December 2020 at National Neurosurgical Referral Center, Bir Hospital, Kathmandu were included in this study. Preoperative and postoperative patient characteristics were recorded. Hormonal remission was defined as normal insulin-like growth factor-1 level at 3 months follow-up.Results: A total of 24 cases were included. The mean age of acromegaly cases was 39.42±10.41 years (24-56 years), with male to female ratio of 0.71:1. Majority (9) of cases had a Knosp grade 1.Thirteen cases had a WilsonHardy Extension Grade 0. Majority (11) of cases had a Wilson-Hardy Invasion Grade I. Three cases developed postoperative CSF leak, which recovered after lumbar drainage with no sequel. Five cases developed epistaxis which resolved with nasal packing. Sixty three percent (15 cases) had normal IGF-1 levels at 3 months follow up.Conclusion: Endoscopic endonasal transphenoidal approach to excision of growth hormone secreting pituitary adenomas is a safe and effective modality at achieving hormonal control in our setting.